Six-year-old boy with a slow-onset persistent back pain. Issue 5 (19th November 2019) - Caddeo, Giulia; Paganin, Paola; Gortani, Giulia; Carbone, Marco; Gregori, Massimo; Barbi, Egidio
Abstract : A 6-year-old boy was evaluated for a 6-week history of low back pain. Initially, the pain was exacerbated by movements, eventually showing a milder and fluctuating trend. History was unremarkable for previous traumatic events, fever or nocturnal pain. Physical examination revealed localised pain at palpation of the spinous processes at the lumbosacral level. Blood tests showed a normal blood count, negative C reactive protein (CRP) and erythrocyte sedimentation rate, normal lactic acid dehydrogenase (LDH) and creatine phosphokinase. A posterior–anterior radiograph of the lumbar spine resulted normal. An MRI scan revealed a lumbosacral transitional vertebra with bone oedema of the posterior arch until the spinous process. For better bone definition, a CT scan was performed ( figure 1 ). Questions: Which causes of persistent low back pain should be ruled out in children under 10 years of age? Osteochondrosis Neoplasm Functional pain Infections What is the diagnosis in this patient? How is the diagnosis performed? How is this condition managed? Answers can be found on page 2.